Interrogating Belonging for Young People in Schools (Springer International Publishing, 2018)
In an era when many young people feel marginalized and excluded, this is the first comprehensive, critical account to shed new light on the trouble of 'belonging' and how young people in schools understand, enact and experience 'belonging' (and non-belonging). It traverses diverse dimensions of identity, including gender and sexuality; race, class, nation and citizenship; and place and space. Each section includes a provocative discussion by an eminent and international youth scholar of youth, and is essential reading for anyone involved with young people and schools. This book is a crucial resource and reference for sociology of education courses at all levels as well as courses in student inclusion, equity and student well-being.